Community-based Utilization and Management of Coastal Areas - Ernawati S. Kaseng (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
The development and management of coastal areas in a sustainable and integrated manner that has not been optimal due to the lack of community participation in maintaining the preservation of coastal resources which still tend to exceed the carrying capacity of the ecosystem. For this reason, this study article aims to describe community-based coastal area management. The study method uses literature studies. Sources and methods of data collection, namely obtained from library data, then read, record, and process and then compile for analysis, and draw conclusions. The results of the study show that the use and management of coastal areas in a sustainable and integrated manner is not optimal because the use of coastal resources still tends to exceed the carrying capacity of the ecosystem, the concept of decentralization and the implementation of legal rules that are still not understood comprehensively by stakeholders. Fisheries and marine development programs and activities in coastal areas are still struggling in an effort to increase catch production. On the other hand, aspects of empowerment and community participation have not been explicitly described in coastal development programs and activities. Community-based coastal area management in the context of economic development of coastal communities related to potential and socio-cultural conditions, requires coastal community development strategies through structural and non-structural approaches through the implementation of training and counseling in coastal community empowerment programs that pay attention to local wisdom.